Unlocking the antimalarial potential of novel steroid-tetraoxane hybrids through consensus molecular docking and molecular dynamics investigation - Dipankar Nath; Abhijit Debnath; Malita Sarma; Rajesh Kumar Singh; Dipak Chetia (Scientific Reports)
Abstract The emergence of Plasmodium falciparum resistance to artemisinin-based combination therapies necessitates the development of novel antimalarial agents. This study presents the first computational investigation of steroid-tetraoxane hybrids targeting cyclophilin, a key protein implicated in artemisinin resistance mechanisms. We designed a library of 127 steroid-1,2,4,5-tetraoxane hybrid compounds combining steroidal sapogenin (∆5,(6)-diosgenin-3-one) and gem-dihydroperoxides, and employed consensus molecular docking across eight platforms to minimize algorithm-specific biases. Compound A-CY-9C emerged as the lead candidate, exhibiting superior binding stability and a favorable free energy landscape during 500 ns molecular dynamics simulations. The dual pharmacophore mechanism—disrupting parasite cholesterol uptake via the steroid component while inducing oxidative stress through the tetraoxane moiety—offers a novel strategy to combat artemisinin resistance. This first-in-class approach to targeting cyclophilin with steroid-tetraoxane hybrids provides a promising foundation for developing next-generation antimalarials against resistant P. falciparum strains.